The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1136/thx.2006.072124
|View full text |Cite
|
Sign up to set email alerts
|

Recorded infections and antibiotics in early life: associations with allergy in UK children and their parents

Abstract: Background: It is suggested that the inverse relationship between allergic disease and family size reflects reduced exposure to early life infections, and that antibiotic treatment in childhood diminishes any protective effect of such infection. Methods: A birth cohort study was undertaken in 642 children recruited before birth and seen annually until the age of 8 years. Reported infections and prescribed antibiotics by the age of 5 years were counted from GP records and comparisons were made with a previous s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 25 publications
(15 reference statements)
2
48
0
Order By: Relevance
“…Taken together, this results in two studies with doubtful results [38,39], three studies in which the association disappeared after correcting for RC [3,40,42], and eight that found a positive association that could not be explained by RC [41,[43][44][45][46][47][48][49].…”
Section: Reverse Causationmentioning
confidence: 52%
See 2 more Smart Citations
“…Taken together, this results in two studies with doubtful results [38,39], three studies in which the association disappeared after correcting for RC [3,40,42], and eight that found a positive association that could not be explained by RC [41,[43][44][45][46][47][48][49].…”
Section: Reverse Causationmentioning
confidence: 52%
“…Four other studies [3,[40][41][42] corrected for RC by means of excluding children who had already developed symptoms at the time of antibiotic use from the analyses. In three of these studies [3,40,42], initially positive associations between antibiotic use and wheeze or asthma disappeared after correction, whereas in the fourth study [41] the association between antibiotic use and wheeze remained after correcting for RC. RC as an explanation was unlikely in six studies that had ensured that exposure (antibiotic use) and follow-up periods took place subsequently and were not overlapping [43][44][45][46][47][48].…”
Section: Reverse Causationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it should be noted that there is no clear relationship between allergic sensitization and allergic symptoms. 17,[51][52][53] Although allergic sensitization often overlaps with the occurrence of allergic symptoms, there are also many children without allergen-specific serum IgE/positive SPT that do develop allergic symptoms 17,19,21,22,26,31 and vice versa. 43 There might be a different …”
Section: Discussionmentioning
confidence: 99%
“…Only 11 of 34 studies included explicitly reported that the use of antibiotics preceded the diagnosis of allergies. 10,12,16,18,21,[25][26][27]37,38,43 In our meta-analysis, we tested the association between antibiotics and risk of hay fever and eczema only in these 11 studies to infer causality and the results still showed a significant association.…”
Section: -56mentioning
confidence: 99%